Type-1 spinal muscular atrophy cohort before and after disease-modifying therapies - Brenda Klemm Arci Mattos de Freitas Alves; Alexandra Prufer de Queiroz Campos Araujo; Flávia Nardes dos Santos; Márcia Gonçalves Ribeiro (Arquivos de Neuro-Psiquiatria)
Background Spinal muscular atrophy (SMA-5q) is a neurodegenerative disease characterized by progressive muscle atrophy, hypotonia, and weakness, with SMA 1 presenting symptoms within the first 6 months of life. Disease-modifying therapies have been approved, with better outcomes with earlier treatment.